Chronic viral hepatitis B and C - Mailliard, Mark (Henry Stewart Talks, 2011)
Diagnosis, Natural History and Therapy of Hepatitis B, Diagnosis, Natural History and Therapy of Hepatitis C
Archived at 2016/07/22